Indicator condition-guided HIV testing in patients with mononucleosis-like illness and community-acquired pneumonia in an Emergency Department setting: A prospective study from Poland (2015–2018) - Karolina Pyziak-Kowalska; Dorthe Raben; Ann Sullivan; Maksymilian Bielecki; Andrzej Horban; Justyna D. Kowalska (PLoS ONE, 2026)
Background Despite advances in HIV care, late diagnosis remains a major public health challenge in Europe, with nearly half of HIV diagnoses in the EU/EEA occurring at a late stage. In Poland, a substantial proportion of people living with HIV remain undiagnosed. Indicator condition–guided testing has been proposed as an effective strategy to reduce missed opportunities for earlier diagnosis. Methods A prospective cohort study was conducted at the Emergency Department of the Hospital for Infectious Diseases in Warsaw, Poland, between May 2015 and March 2018, as part of the European OptTEST project. HIV DUO testing was offered to patients aged 18–65 years presenting with mononucleosis-like illness (MONO) or community-acquired pneumonia (CAP). We evaluated the prevalence of HIV infection and assessed linkage to HIV care among those testing positive. Confirmatory testing, CD4 cell counts at diagnosis, and linkage-to-care outcomes were collected. Results Among 885 patients with indicator conditions (MONO: 794; CAP: 91), 636 (71.9%) accepted HIV testing. Twenty-two patients (3.5%) were confirmed HIV-positive. HIV prevalence was 2.6% among patients with MONO and 11.1% among those with CAP. Most HIV-positive patients were male (90.9%), with 59% identifying as men who have sex with men or bisexual. The median age was 32.5 years. The median CD4 cell count at diagnosis was 341 cells/µL overall and was lower in patients presenting with CAP than MONO (61 vs. 366.5 cells/µL). All patients diagnosed with HIV were linked to care, and 95.5% initiated antiretroviral therapy, with a median time to treatment of 8 days. Conclusions HIV seroprevalence among patients presenting with MONO or CAP was higher than the national average, particularly among those with CAP. These findings support routine indicator condition–guided HIV testing in Emergency Departments to improve early HIV diagnosis and timely linkage to care.